Assessment of The Solvency of Insurance Companies on The Basis of Comprehensive Risk Accounting - Yuliia KOVALENKO; Nataliia TKACHENKO; Raisa KVASNYTSKA; Liudmyla BOHRINOVTSEVA; Oksana HRUBLIAK (Communications of International Proceedings, 2021)
Determining the solvency of insurance companies on the basis of comprehensive consideration of different risk groups is becoming especially relevant in modern financial activity, that requires thorough research of these aspects of the problem. This article contains the types and structuring of the main risks of insurance activity and it also presents their relationships. Methods. The article is based on general scientific methods of cognition especially on such as analysis and synthesis, induction and deduction, system-structural method, quantitative and qualitative comparison, grouping, method of logical generalization. Results. There is proposed a method of assessing the solvency of national insurance companies which is based on the acquired foreign approaches, considering various risk groups such as insurance, market, credit and operational. In order to take into account all the main risks faced by a particular insurer, the estimating technique is subject to significant transformation. A feature of the new system should be a change in approaches to assessing solvency basing on individual risks inherent in a particular insurance company. Conclusion. Practical calculations prove that the new approach proposed by the authors to determine the regulatory solvency, which is based on a set of risks, including insurance, market, credit and operational, requires increased requirements for the actual capital of the insurance company. The main advantage of this approach to assessing the solvency of the company is an analytical assessment of various risks, which allows to improve insurance risk management, control risk positioning in the financial market, effectively manage economic activity and ensure overall financial stability.
Keywords: insurance companies; solvency; insurance risk; market risk; credit risk; operational risk.